PHYSIOLOGICAL STUDIES ON PERFORMANCE OF BT AND NON-BT COTTON (GOSSYPIUM HIRSUTUM) HYBRIDS UNDER DIFFERENT LEVELS OF NITROGEN FERTILIZATION - SIVAKUMARI, B.; MOHAN, JITENDRA (Annals of Agricultural Research, 2014)
A two kharif season field experiment (2007 & 08) was made to study the physiological basis of Bt cotton hybrids superiority under different levels (kg/ha) of nitrogen fertilization (0, 60,120,180) over non-Bt hybrid. Bt cotton hybrids (RCH 317 & RCH 134) with higher crop growth rate during shorter reproductive phase coupled with higher boll retention rate (72.9%) owing to presence of Cry1Ac gene resulted in 47.4% higher seed cotton yields than non-Bt hybrid LHH 144. Each successive increase of 60 kg N up to 180 kg/ha significantly increased leaf area, biomass production, crop growth rate, boll number and boll weight ultimately resulting in markedly higher seed cotton yields.